An Integrated Decision-Making Framework for Enhancing Blockchain Scalability and Efficiency: Layer-2, Off-Chain Storage, and Smart Contracts - Khoa Tan Vo; Hong-Tri Nguyen; Tu-Anh Nguyen-Hoang (IEEE Access)
Blockchain technology has advanced trust and transparency across various sectors, yet persistent limitations remain in scalability, data storage, and smart contract efficiency. Existing research addresses these issues individually, via Layer 2 (L2) scaling, off-chain storage, or contract-level optimizations, but lacks an integrated methodology to guide system-level design. This paper proposes a unified decision-making framework for systematically evaluating and balancing trade-offs among performance, cost, and security across blockchain layers. Drawing on a comprehensive review of foundational and recent literature, the framework introduces quantifiable metrics, including the Scalability Necessity Factor (ScaNF), the Cost Efficiency Factor (CEF), and the Security Necessity Factor (SecNF), to support architecture-level decisions. Through formalized evaluation criteria, it enables developers to identify when and how to adopt L2 rollups, off-chain storage models, and smart contract optimizations. The framework is positioned as a generalizable tool for designing efficient, scalable, and secure blockchain applications in practice.